Characteristics of Regional Cerebral Blood Flow in Alzheimer Disease and Amnestic Mild Cognitive Impairment by Single-Photon Emission Computerized Tomography: A Cross-Sectional Study - Kunieda, Yota; Arakawa, Chiaki; Yamada, Takumi; Suzuki, Mizue; Koyama, Shingo; Kimura, Yosuke; Ichikawa, Takeo; Shino, Shuhei; Yamada, Minoru; Hirokawa, Ryuto; Matsuda, Tadamitsu; Takakura, Tomokazu; et al. (Dementia and geriatric cognitive disorders extra, 2021)
Introduction: The regional cerebral blood flow (rCBF) distribution can affect brain functioning, leading to amnestic mild cognitive impairment (aMCI) and mild Alzheimer disease (AD). This study aimed to clarify the detailed characteristics of rCBF distribution in patients with mild AD and aMCI. Methods: This cross-sectional study from April 2015 to March 2018 included 103 older adults (mean age 78.9 years; 60% females), out of a total of 302 adults, and categorized them into 3 groups according to cognitive symptoms. The normal control (NC), aMCI, and mild AD groups included 20, 50, and 33 participants, respectively. The primary outcome was rCBF, which was compared among the 3 groups using a 2-sample t test without correction for multiple comparisons. Results: In the aMCI group, the rCBF decreased in the bilateral parietal and left frontal association cortex and the bilateral premotor cortex (p < 0.01) but increased in the bilateral cerebellum (p < 0.01). In the mild AD group, the rCBF decreased in the bilateral parietal and occipital association cortex, the bilateral premotor cortex, the left temporal and frontal association cortex, and the left limbic lobe (p < 0.01). Conversely, the rCBF increased in some parts of the cerebellum, the bilateral frontal and temporal association cortex, the left occipital association cortex, and the right premotor cortex (p < 0.01). Conclusion: Based on the analysis of the values obtained, it was inferred that the rCBF undergoes reduction and elevation in aMCI and AD patients.